SUGARCANE COMPANY. EVALUATION MODEL: ACQUISITION AND MAN-AGEMENT COMPANY SUPPLIERS BASED ON THE ITEM 7.4 OF ISO 9001:2008 - GEBARA, A.T.J.; CARASCHI, J.C.; PRATES, G.A.; DE CAMPOS, C.I.; FERREIRA, B.S. (Revista Brasileira de Engenharia de Biossistemas, 2014)
This study was conducted, based on the case study, which was aimed to analyze the compliance with standards and requirements of this standard company. For instance, the sugarcane industry. The work was conducted by a questionnaire, based on standard ISO 9001:2008, item 7.4. in question for allowing to know the organizational impacts. Such as, improved quality and standardization of products and processes. Along with greater customer satisfaction and better relationships with partners. As well as; providing the existence of a model qualification criteria, seeking to identify suppliers that demonstrate evidence of compliance to specify requirements and the existence of vendor evaluation criteria, which aims to verify compliance when compared to specified requirements.